2011
DOI: 10.1364/oe.19.026295
|View full text |Cite
|
Sign up to set email alerts
|

Coupled simulation of chemical lasers based on intracavity partially coherent light model and 3D CFD model

Abstract: Abstract:Coupled simulation based on intracavity partially coherent light model and 3D CFD model is firstly achieved in this paper. The dynamic equation of partially coherent intracavity field is derived based on partially coherent light theory. A numerical scheme for the coupled simulation as well as a method for computing the intracavity partially coherent field is given. The presented model explains the formation of the sugar scooping phenomenon, and enables studies on the dependence of the spatial mode spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, a random noisy input field is necessary when apply this iterative propagation method to stable resonators with high Fresnel numbers [ 12 , 13 ]. Assuming the amplitude of a input field is u 0 ( x, y ), the random noise is added in following form: where rand ( x, y ) is a random number in the range 0–1 generated by computer programs, u 0 ( x, y ) is the initial field produced by spontaneous radiation of excited atomic iodine.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a random noisy input field is necessary when apply this iterative propagation method to stable resonators with high Fresnel numbers [ 12 , 13 ]. Assuming the amplitude of a input field is u 0 ( x, y ), the random noise is added in following form: where rand ( x, y ) is a random number in the range 0–1 generated by computer programs, u 0 ( x, y ) is the initial field produced by spontaneous radiation of excited atomic iodine.…”
Section: Methodsmentioning
confidence: 99%
“…The results [11,12] do not show any mixing and nozzle tail flow effect imprints on the flow or optical fields as seen in [8,9] ; perhaps the grid is not fine enough to resolve them.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have shown reasonable comparisons with measured gain, power and dissociation data [7][8][9][10][11][12] , they have provided incomplete insight into some of the fluid dynamic effects within COIL flow fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics, such as good atmospheric propagation, short wavelength and excellent transmission through optical fibers, make the COIL a good candidate for high power laser application. Simulations [3][4][5][6] of chemical lasers such as COIL are of timely interest due to the need to understand the physics underlying the COIL so that its performance may be optimized.…”
Section: Introductionmentioning
confidence: 99%